Utilization of Recycled Demolition Concrete (International Journal of Engineering and Computer Science, 2014)
India is presently generating construction and demolition (C & D) waste to the tune of 23.75million tones annually and these figures are likely to double fold in the next 7 years. C & D waste and specifically concrete has been seen as a resource in developed countries.  Works on recycling have emphasized that if old concrete has to be used in second generation concrete, the product should adhere to the required compressive strength.  This paper deals with the review of the existing literature work for the use of recycled concrete as aggregates in concrete in respect of mainly the compressive strength and proposes and approach for use of recycled concrete aggregate without compromising the strength.  The need for demolition, repairs and renewal of concrete and masonry structures is rising all over the world, more so in the developing countries.  It is highly desirable that the waste materials of concrete and bricks of further reutilized after the demolition of old structures in an effective manner especially realizing that it will help in reducing the environmental damages caused by excessive reckless quarrying for earth materials and stones.  Secondly, this will reduce pressure on finding new dumping ground for these wastes, thus further saving the natural environment and ecosystem.  This paper critically examines such properties in reused concrete and brick masonry waste materials and suggests suitable recommendations for further enhancing life of such structures thereby resulting in sufficient economy to the cost of buildings.